Students' Perceptions on Physical Education Teachers' Compliance with the Professional Code of Ethics and Conduct in Tanzania - Stephen Mabagala (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2016)
The nature of Physical Education (PE) is grounded in movements, games and sports; this lends itself to a high rate of interaction between PE teachers and students. As such, PE teachers need to be aware and comply with their professional code of ethics and conduct (PCEC) in their relationship with students during theory and practical lessons as well as during interschool competititons and outside school contexts. The idea of PE teachers' compliance with PCEC in Tanzania has not been widely investigated, so this study is rare and important to the field. The purpose of the study was to determine the perception of students on PE teachers' compliance with PCEC in Tanzania. The study utilized descriptive survey design and was conducted in secondary schools and teachers' colleges that had PE and sport programs. Purposive sampling was adopted to select PE students and data were collected through a questionnaire. Participants were 720 students who were either studying PE or participating in school sports. It was concluded that PE students perceive their teachers as having a high level of compliance with the PCEC and their perception is influenced by their level of education. It was recommended that there is a need to improve and sustain PE programmes in schools and colleges, emphasize training in the codes for teachers, and moral education for students. There is also a need to improve teacher-student-relationship and school-community partnerships through sports. Further study should be conducted to determine unethical behavior in teacher-student relationships in the context of school sport.